PENGARUH PEMBERIAN MAKANAN TAMBAHAN PEMULIHAN (PMT-P) TERHADAP PERUBAHAN SKOR Z BERAT BADAN MENURUT UMUR BALITA GIZI KURANG (Studi di Wilayah Kerja Puskesmas Makki Distrik Makki Kabupaten Lanny Jaya - Papua Tahun 2017) - Merry Wenda; Siti Fatimah Pradigdo; M . Zen Rahfiludin; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Underweight is one of the major nutritional problems in Indonesian under five year. Prevalence of underweight increases at the age of 6 to 11 months and it peaks at the age of 12 to 35 months. Hence, one of the efforts made to overcome it is recovery supplementary feeding. The aim of this study was to analyze the effect of recovery supplementary feeding on a change in weight/age z score of underweight under five year at the age of 6 to 59 months at Makki Community Health Center, Makki Sub-District, Lanny Jaya District. This study was. Quasi-Experiment Research with Pretest and Posttest One Group Design approach. Subjects were 30 underweight under five year at the age of 6 to 59 months. The result showed that difference of weight/age Z score means before and after recovery supplementary feeding was 2,2593 with SD 0,046. Weight/age z score of under five year before intervention was 30 underweight subjects (100%) and became 27 normal subjects (90%) after interventions. There was a difference of change in weight/age z score before and after recovery supplementary feeding which was the highest increase of 3,5% and the lowest increase of0,3% of weight before supplementary feeding. Wilcoxon Signed Rank Test showed there was a significant effect of recovery supplementary feeding on a change in weight/age z score of underweight under five year at the age of 6 to 59 months at Makki Community Health Center, Makki Sub-District, Lanny Jaya District(p < 0,05).